A organização social e educativa das mulheres da aldeia Pimentel Barbosa : uma etnografia das educadoras piõ A’uwẽ (mulheres Xavante) - Rezende, Maria Aparecida (2012)
This thesis aims to record systematically the world of female A’uwẽ education focusing in documenting their daily lives. The research shows the maximum possible development of their activities and it becomes itself like an instrument of school research like the women desire, so the indigenous teachers can encourage and strengthen, with children and young women, the continuity of this traditional work that the elderly A'uwẽ women send over their generations. The method was chosen by the women guiding the research in the context of the village. It is an open research of ethnographic nature, passing by phenomenological analysis and thought in a philosophical Merleau-Ponty context with the Geertz' interpretive anthropology and the Mauss´ sociology. There is absolute timing between Geertz and Merleau-Ponty, the lack of a part that is not somehow intertwined with the other. Geertz insists to declare openly this complicity in such a way that the omission of it does not mislead the alleged objectivity that can be used by the researcher with ill intent. There is not also in Merleau-Ponty an absolute reduction that can separate the links between researcher and researched, between the subject and object or other subjects. The research in question follows the desire announced by elderly women and it should be connected and submitted to the strengthening of A’uwẽ culture. At this time the thesis is organized in four parts and they are composed of chapters. Initially, I offer the methodology and the introduction followed by Part I - "Ethnography and the construction of the research" brings in their batch two chapters: 1. "A dense description of the time lived during the research" and 2 "back to the Village Pimentel Barbosa". In the part II - "The world of Xavante women and their historical, political and cultural contexts" in two chapters: 1. "The A'uwẽ from Goias to Mato Grosso" and 2. "The life of Xavante women in a general context". Part III - "The revelations of a dense description: the dialog between the lived world and thought world ". It is accompanied by five chapters. 1. "Stages of women life"; 2. "The exchanges and the gifts between Xavante and non-indigenous"; 3. "The vegetation in the women life and the king buriti"; 4. "The A'uwẽ female hard work and the voices of silence”; chapter 5. "The participation of women in the celebration of male ears piercing: initiation of the young men". The last part "The end of a carretel and the need to conduct to other" is the attempt to close the text, conscious of an unfinished research that will be continued to describe the contexts that show the women life and education in this society that has much things to give to the education and the social and political organization of western society.